Conditions that Stabilize Membrane Domains Also Antagonize n-Alcohol Anesthesia - Machta,BB; Gray,E; Nouri,M; McCarthy,NLC; Gray,EM; Miller,AL; Brooks,NJ; Veatch,SL (Biophysical Journal, 2016)
Diverse molecules induce general anesthesia with potency strongly correlated with both their hydrophobicity and their effects on certain ion channels. We recently observed that several n -alcohol anesthetics inhibit heterogeneity in plasma-membrane-derived vesicles by lowering the critical temperature (Tc) for phase separation. Here, we exploit conditions that stabilize membrane heterogeneity to further test the correlation between the anesthetic potency of n -alcohols and effects on Tc. First, we show that hexadecanol acts oppositely to n -alcohol anesthetics on membrane mixing and antagonizes ethanol-induced anesthesia in a tadpole behavioral assay. Second, we show that two previously described “intoxication reversers” raise Tc and counter ethanol’s effects in vesicles, mimicking the findings of previous electrophysiological and behavioral measurements. Third, we find that elevated hydrostatic pressure, long known to reverse anesthesia, also raises Tc in vesicles with a magnitude that counters the effect of butanol at relevant concentrations and pressures. Taken together, these results demonstrate that ΔTc predicts anesthetic potency for n-alcohols better than hydrophobicity in a range of contexts, supporting a mechanistic role for membrane heterogeneity in general anesthesia.